Gezi park protests in Turkey: how can death be related to the protests?. Issue 4 (3rd July 2016) - Koca-Atabey, Müjde
Abstract: The aim of the paper is to investigate the Gezi Park Protests in Turkey from the perspective of terror management theory (TMT). The Gezi Park Protests started at the end of May 2013 to defend the destruction of a small park. The protests started with environmentalist reactions and acquired a political nature afterwards. The roles of social media and humour are also discussed in relation to the different dimensions of the Gezi Park Protests. TMT, more specifically the mortality salience hypothesis, is used to explain these protests, since they include both the concrete and abstract forms of mortality. The concrete forms of death were the death of trees and the death of protesters themselves. The abstract forms of death, on the other hand, were the death of lifestyle from the protesters' perspective and death of exercise power from the government's side. Three necessary conditions for an alternative experimental manipulation in TMT studies are discussed in relation to the Gezi Park Protests. It is concluded that the protests provided a concrete and real-life example of TMT.